Effects of phosphorus stress on the photosynthetic and physiological characteristics of Chlorella vulgaris based on chlorophyll fluorescence and flow cytometric analysis. (July 2017) - Jiao, Yang; Ouyang, Hui-Ling; Jiang, Yu-Jiao; Kong, Xiang-Zhen; He, Wei; Liu, Wen-Xiu; Yang, Bin; Xu, Fu-Liu
Highlights: The effects of phosphorus on Chlorella vulgaris in photosynthesis and physiology are studied. Lack of orthophosphate affected the electron receivers and donators in PSII system simultaneously. Phosphorus stress could result in inhibition of the cell yield rather than cell death. Phosphorus stress could also decrease the esterase activities and increase the size of algal cells. Abstract: This paper discusses the effects of phosphorus stress on the photosynthetic and physiological characteristics of Chlorella vulgaris . The results indicate that the growth and photosynthesis of C. vulgaris were affected under non-phosphorus control and non-orthophosphate treatments (pyrophosphate, tripolyphosphate and glycerophosphate). Orthophosphate promoted the growth of C. vulgaris most significantly, while the growth of C. vulgaris under non-phosphorus control was slow and soon entered a stable period. The growth of C. vulgaris was also promoted under non-orthophosphate treatments, but slower than orthophosphate treatment, with no significant differences among the three. A reversible inactivation occurred in the PSII system of C. vulgaris under non-phosphorus control after 24 h, while the same phenomenon occurred after exposure for 7 days under non-orthophosphate treatments. The decrease in actual photochemical efficiency was related to the fall in the ratios of the opening reaction centers in the PSII system. For non-orthophosphate treatments, it was also related to other factors, as not all opening reaction centers transferred electrons. Phosphorus stress did not affect the integrity of the cell membranes, demonstrating that phosphorus stress could result in the inhibition of cell yield, rather than cell death. Phosphorus stress could also decrease the esterase activities and increase the mean size of algal cells.